Estudo da morfodinâmica sazonal e quantificação de transporte sedimentar costeiro nas praias de Fortalezinha e Princesa, Algodoal/Maiandeua (nordeste do estado do Pará) - SILVA, Paulo Victor Magno (Universidade Federal do Pará, 2019)
Understanding the processes responsible for the morphodynamics of the coastal environments and sediment transport is necessary considering that such processes play an important role in the formation and stabilization of the beach. The coastal zone is a complex, dynamic and unstable range in which is subject to continuous changes generated by coastal morphodynamic processes such as winds, waves, tides and tidal currents. This Master thesis shown the morphodynamics and transport measurement of sediment in macrotidal on the Princesa and Fortalezinha beaches (Pará coast). These beaches are part of the sandy plains, around the Algodoal/ Maiandeua island (Maracanã city), being inserted in the Salgado Atlantic Coast of Pará. Two data collection campaigns were conducted: (i) in the dry season (15 - 19/10/2012) and; (ii) in the rainy season (13 - 16/03/2013). To analyze the morphological variation of these beaches and its erosive trends and / or accretion, were executed 8 topographic profiles (4 in each beach). At the same time the survey of profiles, sediment samples and measurements of hydrodynamic parameters (waves and currents) were performed. To quantify the coastal sediment transport were used two methods: (1) “traps” for aeolian sediment transport in each profile, and (2) “portable traps” for longitudinal transport in the surf zone, over three different sectors of the beaches. These beaches are composed predominantly of fine and well selected sand. The beaches exhibited low slope (<2 °) for the two periods. In the dry period was observed on the Princesa beach one well developed bar-rip in the middle intertidal zone, characteristic of dissipative beaches, while in the rainy season occured loss of sediment in this area, allowing the exposure of a muddy terrace (paleomangrove) in the central sector. In general, the Princesa and Fortalezinha beaches are subject to a semidiurnal macrotidal regime. The active winds have preferred direction of E in less rain season and NE in the rainy season period, with sliding dominant waves of low period and NE direction. The coastal currents have preferred NW direction, with variations during the tidal cycle. The active winds have preferred direction E in less rainy period and NE in the rainy season. During the dry season the beaches have intermediate characteristics beaches, with Ω between 4.322 to 4.579 on the Princesa beach and 4.074 to 4.668 in the Fortalezinha beach. During the rainy season were characterized as dissipative, with Ω ranging from 5,088 to 6,763 values on the Princesa beach and 5.790 to 6.174 on the Fortalezinha beach, with only the NE sector of the Princesa beach with intermediate characteristics. The Princesa beach evolved from ultradissipative beach state (7 <RTR <15:02 <Ω <5)(dry season) to the dissipative state without bars (3 <RTR <7 and Ω> 5)(rainy period). However, the Fortalezinha beach had its status as an intermediary with low-water channel-bar system (3 <RTR <7:02 <Ω <5) in the dry season, and dissipative and no bars (3 <RTR <7 and Ω> 5), in the rainy season. On the beaches is bidirectional longitudinal transport however in the rainy season the beach was characterized as dissipative and no bars (3 <RTR <7 Ω and> 5). On the beaches is bidirectional longitudinal transport, with resulting NW. The direction of the longitudinal current and longshore drift is influenced, respectively, by the direction and intensity of the trade winds from the NE (dry season) and tidal currents (rainy season). The aeolian transport is a function of the intensity and duration of winds and rains mainly, however, in the dry season this is high due to strong winds, and the lack of rain makes the sediments of less cohesive swash zone and easier to be transported. The coastal dynamics on the beaches is influenced by the adjacent drainages (rivers and tidal channels) especially during the ebb tide. During the rainy season, the Marapanim and Maracanã rivers flow is high, due to increased rainfall in the headwaters of rivers, increasing the export of continental sediments (silt and clay) for the coastal region, and are incorporated into coastal drift and deposited in beaches during times of low energy, along with sandy sediments mainly from adjacent continental shelf by tidal currents.